Comparison of 2 new real‐time polymerase chain reaction–based urinary markers in the follow‐up of patients with non–muscle‐invasive bladder cancer. Issue 5 (24th January 2020) - Trenti, Emanuela; Pycha, Stefan; Mian, Christine; Schwienbacher, Christine; Hanspeter, Esther; Kafka, Mona; Spedicato, Giorgio Alfredo; Vjaters, Egils; Degener, Stephan; Pycha, Armin; D'Elia, Carolina
Abstract : Background: The objective of the current study was to compare the diagnostic accuracy of 2 new real‐time polymerase chain reaction–based urinary markers with each other and with urinary cytology, cystoscopy, and/or histology in patients being followed for non–muscle‐invasive bladder cancer. Methods: A total of 487 patients were enrolled in the study. Patients were evaluated using voided urine cytology, the Xpert Bladder Cancer Monitor, the Bladder EpiCheck test, and white light cystoscopy. Results: The overall sensitivity was 27.17% for cytology, 64.13% for the Bladder EpiCheck test, and 66.3% for the Xpert Bladder Cancer Monitor. The overall specificity was 98.82% for cytology, 82.06% for the Bladder EpiCheck test, and 76.47% for the Xpert Bladder Cancer Monitor. The negative predictive value was very similar for the 3 tests at 83.56% for cytology, 89.42% for the Bladder EpiCheck test, and 89.35% for the Xpert Bladder Cancer Monitor. When combined, the Bladder EpiCheck test and Xpert Bladder Cancer Monitor detected overall 79.35% of the tumors: 70.37% in low‐grade and 92.11% in high‐grade tumors. Conclusions: The Xpert Bladder Cancer Monitor and Bladder EpiCheck test were found to perform very well in terms of sensitivity. Together, the 2 tests detected approximately 92.11% of high‐grade tumors. Their specificity was high but could not reach the excellent value of cytology. The negative predictive value was the same for both tests and was higher than that for cytology, especially when the tests were used together (92.24%). These 2 new tests hold promise as urinary biomarkers. They may be used in combination to maximize sensitivity in a less invasive way, thereby reducing invasiveness in the follow‐up of patients with non–muscle‐invasive bladder cancer and decreasing discomfort for the patients as well as complications and costs. Abstract : The Bladder EpiCheck test and Xpert Bladder Cancer Monitor are promising urinary markers. They may be used in combination with cytology to reduce invasiveness in the follow‐up of patients with non–muscle‐invasive bladder cancer, thereby decreasing discomfort for the patients as well as complications and costs.